Changes in the carriage and traffic capacity along highly busy routes in case of traffic scheduling for permanently linked multiple trains - Evgeniy A. Sotnikov; Pavel S. Kholodnyak (Вестник Научно-исследовательского института железнодорожного транспорта)
The increase in transportation volume through the railroad network requires novel less capital-intensive methods for increasing the carriage capacity with respect to the busy routes that operate at traffic capacity levels of 0.8 and higher. One proposed method is the traffic scheduling of permanently linked multiple trains. Because the existing lines were constructed without considering the usage of permanently linked multiple trains, special preparation of various sections, especially for enhancing the electric power supply system, as well as additional development of stations are required. Compared with single trains, the increase in the length of the linked trains reduces the traffic capacity, affecting the carriage capacity. Further, the peculiarities of interval changes, including the succession times at sections, arrival spacing, and train departure from a station while scheduling linked train traffic on a permanent basis on busy lines, were analyzed. This served as the basis for determination of parameters for the changing traffic and carriage capacity of single and double tracks or traffic routes in general. All the aforementioned intervals increased on the double-track lines, which reduced their traffic capacity. Furthermore, the section occupation duration increased for the linked trains on single-track lines; accordingly, a traffic scheduling period can be established for determining the reduction in traffic capacity. The main station intervals of the single-track traffic schedule of not simultaneous train arrival with the stop and the opposite train without stop are not changed. Some calculation options were introduced for altering the traffic and carriage capacity of the busy lines for different running speeds of trains, shares of linked trains in the total amount of freight transportation, and shares of traffic capacity with respect to passenger traffic. Further, calculations were performed by considering that all the technical infrastructure facilities and rolling stock satisfy the system requirements for arrangement of the linked train traffic on a permanent basis. The usage of this method increases the capacity of the busy routes, reduces the traffic capacity by 1%-6% and increases the carriage capacity by 4%-27% for linked trains with the share from 5% to 40%. This indicates that the method for permanent scheduling of the linked train traffic is a novel method for increasing the carriage capacity along the busy routes.